Strategi Pemasaran Produk Pengolahan Kayu Pada Mebel UD. Mayusbri di Kecamatan Maulafa Kota Kupang - Suryani Suryani; Nixon Rammang; Pamona S. Sinaga; Lusia Sulo Marimpan (Wana Lestari, 2026)
The purpose of this study is to determine effective marketing strategies to increase sales of processed wood products in the UD. Mayusbri furniture industry and to determine the opportunities and challenges in marketing processed wood products in the UD. Mayusbri furniture industry. UD. Mayusbri furniture business is a furniture business founded by Mr. Martinus Pasanda Borong in 2003, which is located in Fatukoa Village, Maulafa District, Kupang City. This type of research is field research, which is a type of research that studies phenomena in their natural environment. This research is qualitative in nature, which is research conducted in certain settings that exist in real life with the intention of finding out in depth and understanding a phenomenon. The data collection techniques used are observation and interviews. The collected data are then analyzed using the SWOT analysis method. The results of the study indicate that an effective marketing strategy to increase sales of processed wood products in the UD. Mayusbri furniture industry is the SO (Strength-Opportunities) strategy, namely by maintaining existing strengths and making the most of existing opportunities. Several things need to be done to implement this strategy, namely, first, maintaining product quality, as well as adding strategic marketing locations and ensuring consumer satisfaction with quality products. Second, maintaining good relations with raw material suppliers. Third, ensuring that production activities continue to run by utilizing existing technology. Opportunities that can be utilized are the high level of consumer satisfaction with the products produced and the potential for online markets. Meanwhile, the challenges faced are the scarcity of raw materials, the emergence of new competitors, changes in consumer tastes, increasing raw material prices, and limitations in the use of information technology